Pengaruh Kehadiran Guru Terhadap Minat Belajar Siswa di MTS Raudlatul Wathoni Taman Sari: The Influence of Teacher Presence on Student Learning Interest at MTs Raudlatul Wathoni Taman Sari - Zakaki (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
Education plays a crucial role in developing the quality of human resources, and it can also support the achievement of national development. Achieving national development through education requires the empowerment of qualified human resources. This study aims to determine the influence of teacher presence on student learning interest. This type of research uses quantitative research using an expostfacto approach. The sample of this study was 66 students of MTS Raudlatul Wathoni Taman Sari consisting of three classes, namely VII, VIII, and IX with a total population of 66 students. In collecting data, researchers used questionnaires and documents as instruments. The data analysis technique used a descriptive data analysis method carried out with the steps of normality testing, homogeneity testing, and hypothesis testing. After collecting and processing the data, researchers found that the hypothesis test showed r count = 1.284 and r table = 0.224. Thus, the initial hypothesis (Ha) was accepted and the alternative hypothesis (Ho) was rejected. Thus, it can be concluded that there is a positive and significant influence between teacher presence and student learning interest at MTS Raudlatul Wathoni Taman Sari.